The mouse pubic symphysis: a narrative review - Wang, Ning; Tong, Xue; Li, Yi-kai (Frontiers in Physiology, 2025)
Remodeling and relaxation of the mouse pubic symphysis (PS) are responsible for separating the pubic bone, allowing the passage of the full-term fetus, and ensuring safe delivery. PS in postpartum mice can rapidly return to a similar non-pregnant state, providing mechanical stability for the reproductive tract. During pregnancy and postpartum recovery, PS changes in mice are involved in many aspects, including extracellular matrix (ECM), matrix metalloproteinases (MMPs), cell phenotypes, hormones, and immune cells. The changes in PS in mice during pregnancy and postpartum convalescence were reviewed, and the possible mechanisms were discussed. We hope to attract more research interest to explore the biological mechanisms of this process better.